Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian - D. Muhammad Yamin (E-Journal Studia Manajemen, 2023)
This study aims to determine the effect of product quality and price on purchasing decisions on SkinCare dr. Henny Chaerani Rangkasbitung. The research method used is quantitative research. The samples that were used as research objects were 99 respondents. Data collection techniques using Observation, Documentation, Library Stady, Questionnaires. The population in this research is all consumers in 2019-2021, totaling 11,363 people, resulting in a sample of 99 people using the slovin formula. Data analysis techniques used are: Validity Test, Reliability Test, Classical Assumption Test, Normality Test, Multicollinearity Test, Hetroscedasticity Test, Autocorrelation Test, Analysis Test, Multiple Linear Regression Test, Correlation Test, Detrimination Coefficient Test (R2) Hypothesis Test, Test T (Partial), Test F (Simultaneous) with the help of Software Statistical Package For The Social Science (SPSS) V20.